2009
DOI: 10.1007/s10508-009-9541-3
|View full text |Cite
|
Sign up to set email alerts
|

The DSM Diagnostic Criteria for Transvestic Fetishism

Abstract: This paper contains the author's report on transvestism, submitted on July 31, 2008, to the work group charged with revising the diagnoses concerning sexual and gender identity disorders for the fifth edition of the American Psychiatric Association's Diagnostic and Statistical Manual of Mental Disorders (DSM). In the first part of this report, the author reviews differences among previous editions of the DSM as a convenient way to illustrate problems with the nomenclature and uncertainties in the descriptive p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 25 publications
1
33
0
Order By: Relevance
“…Yet another study (Blanchard, 2010a), which used a separate sample, concerned the proposed diagnosis of Transvestic Disorder (presently called Transvestic Fetishism). Its results showed that male transvestic patients who acknowledged autogynephilia (the tendency to be sexually aroused by the thought or image of themselves as women) had almost five times higher odds of reporting past or current desires for sex reassignment than transvestic patients who denied autogynephilia.…”
mentioning
confidence: 99%
“…Yet another study (Blanchard, 2010a), which used a separate sample, concerned the proposed diagnosis of Transvestic Disorder (presently called Transvestic Fetishism). Its results showed that male transvestic patients who acknowledged autogynephilia (the tendency to be sexually aroused by the thought or image of themselves as women) had almost five times higher odds of reporting past or current desires for sex reassignment than transvestic patients who denied autogynephilia.…”
mentioning
confidence: 99%
“…As part of the American Psychiatric Association's (APA) process of revising the Diagnostic and Statistical Manual of Mental Disorders (DSM), Blanchard (2010a), the chair of the DSM-5 Paraphilias subworkgroup (PSWG), has proposed a new paraphilia definition: ''A paraphilia is any powerful and persistent sexual interest other than sexual interest in copulatory or precopulatory behavior with phenotypically normal, consenting adult human partners'' (p. 367). 1 Blanchard (2009a) acknowledges that his paraphilia ''definition is not watertight''and it already has attracted serious criticism (see Haeberle, 2010;Hinderliter, 2010;Singy, 2010).…”
mentioning
confidence: 99%
“…For instance, Thornton, an official advisor to the DSM-5, claims that a paraphilia is ''an abnormal sexual interest,'' adding matter-of-factly that ''what counts as 'abnormal' is culturally relative'' (Thornton, 2010, p. 411). Blanchard (2010), the Chair of the Paraphilias Subwork Group, defines a paraphilia as ''any powerful and persistent sexual interest other than sexual interest in copulatory or precopulatory behavior with phenotypically normal, consenting adult human partners''(p. 367). Although it is difficult to make sense of this hodgepodge definition, one thing seems clear: some kind of cultural norm must be the glue that holds together the odd conjunction of copulation (a behavior), consent (a legal concept), and phenotypical normality (whatever that means).…”
mentioning
confidence: 99%